2017
DOI: 10.1161/atvbaha.117.309999
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ (Transforming Growth Factor-β) Blockade Induces a Human-Like Disease in a Nondissecting Mouse Model of Abdominal Aortic Aneurysm

Abstract: Endogenous TGFβ activity is required for the healing of AAA. TGFβ blockade may be harnessed to generate new models of AAA with better relevance to the human disease. We expect that the new models will improve our understanding of the pathophysiology of AAA and will be useful in the identification of new therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 30 publications
3
83
1
1
Order By: Relevance
“…During the progression of AAA, accumulation, and activation of inflammatory cells takes place in the aorta. These inflammatory cells play a key and substantial role in vascular remodeling 9,29 . In our study, we found a significant amount of CD 68 (M1 type macrophage) and activated macrophage Mac-2 in PPE treated aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the progression of AAA, accumulation, and activation of inflammatory cells takes place in the aorta. These inflammatory cells play a key and substantial role in vascular remodeling 9,29 . In our study, we found a significant amount of CD 68 (M1 type macrophage) and activated macrophage Mac-2 in PPE treated aorta.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ1 plays a key role in the progression of aneurysm. Others have shown that TGFβ1 administration exacerbates aneurysms 20,9 . IHC staining for TGFβ1 was performed to assess the presence of TGFβ1 in the aneurysmal aorta, in PPE and PGG treated aorta sections.…”
Section: Pgg Treatment Decreases Tgfβ1 In the Aneurysmal Aortamentioning
confidence: 99%
“…30 Details on the development and characterisation of these mouse models have been previously published. 29,30 Procedures. For all experiments, we used male, C57Bl/6J, 8-week-old mice (Charles River, UK).…”
Section: Experimental Mouse Modelsmentioning
confidence: 99%
“…Arrows = free ends of ruptured media. C ) Schematic of the new murine AAA model reported by Lareyre et al 14 Elastase is applied topically to the abdominal aorta, and mice are injected with anti-TGF-β antibodies. Aortas undergo medial degeneration with breaks in elastic laminae (arrows) as well as dilation that includes all 3 layers (intima, media, adventitia).…”
Section: Figurementioning
confidence: 99%
“…14 They suggest that none of the existing animal AAA models “reproduces and combines the major features of human AAA,” which they list as: extracellular matrix proteolysis, degeneration and loss of vascular smooth muscle cells, alteration of endothelial cells, intraluminal thrombosis, infiltration of innate and adaptive immune cells, progressive aortic dilation in the absence of medial dissection, and aortic wall rupture. Lareyre et al criticize current animal AAA models as either: 1) models of intramural hemorrhage/dissection without true aneurysmal dilation [e.g., the angiotensin II-infusion model (Figure) as well as models relying on lysyl oxidase inhibition or mineralocorticoid agonists combined with high salt); or 2) models of aortic dilation that fail to progress to rupture (e.g., the elastase or calcium chloride models).…”
mentioning
confidence: 99%